HUBUNGAN FREKUENSI "NGEMIL", KONSUMSI JUNK FOOD, SCREEN TIME DENGAN KEJADIAN OVERWEIGHT PADA MAHASISWA UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Sulistyani Meita Dewi, (2020)
Background : Adolescence is the limit of the transition of life from children and adults. Modern lifestyle will lead to adolescent nutritional status above normal, so that a teenager will become more nutritional status. This is because teenagers eat a lot but do not do physical activity so what happens is the energy that enters the body is not appropriate and far more than the energy used for activity and growth period. The objective: Of this study was to identify the relationship between "Snacking" Frequency, Junk Food Consumption, Screen Time with Overweight Events in UPN Veteran Jakarta Students. Method: The method in this research is quantitative and uses cross sectional design. The sample in this study were 38 samples with Simple Random Sampling technique. The instrument in this study was to use a questionnaire. Results: Based on the results, there were 36.8% of respondents with over nutrition. Based on bivariate results performed using the chi square test showed a relationship between Junk Food Consumption (p = 0.014) and Screen Time (p = 0.030) with Overweight events. Meanwhile, the frequency of "snacking" there was no relationship with the incidence of overweight (p = 0.093). Conclusion: There is a relationship between Junk Food Consumption and Screen Time with the incidence of overweight in adolescents. There is no relationship between the frequency of "snacking" with the incidence of overweight in adolescents.